SEDIMENT DEPOSITION IN A SOUTH SULAWESI SEAGRASS BED - Lanuru, Mahatma; Fitri, Ramdina (Marine Research in Indonesia, 2008)
Deposition of suspended sediment was measured with sediment traps in shallow coastal waters colonized by Thallasia dominated seagrass in Pannikiang Island, South Sulawesi (Indonesia). The primary objective of this study was to compare the amounts of sediment deposition inside seagrass beds and in adjacent unvegetated area. The traps were placed in a seagrass bed (Station I, II, and III) and in an adjacent unvegetated area (Station IV) measuring the sediment flux on the seabed. The sediment fluxes due to deposition were significantly higher at stations I and II (P < 0.05) and station III (P < 0.01) than at station IV (unvegetated area). Results of this study suggest that sediment deposition was promoted by dense shoots of seagrass. The study provides quantitative evidence for the importance of seagrass bed as sites of sedimentation of fine particles. Â